Combined treatment of nonsmall cell lung cancer NSCLC stage III with intensity-modulated RT radiotherapy and cetuximab: the Near trial - Jensen, Alexandra; Münter, Marc; Bischoff, Helge; Haselmann, Renate; Haberkorn, Uwe; Huber, Peter E.; Thomas, Michael; Debus, Jürgen; Herfarth, Klaus (Cancer, 2011)
BACKGROUND: The aim of this study was to evaluate efficacy and toxicity of radioimmunotherapy with intensity-modulated radiation (IMRT) and cetuximab in stage III nonsmall cell lung cancer (NSCLC). METHODS: NEAR was a prospective, monocentric phase II trial including patients unfit for chemoradiation regimen; treatment consisted of IMRT and weekly cetuximab followed by a 13-week maintenance period. Primary endpoints were toxicity and feasibility; secondary endpoints were remission rates at completion of the planned treatment according to Response Evaluation Criteria In Solid Tumor (RECIST), local/distant progression-free survival, and overall survival. RESULTS: Thirty patients (median age, 71 years) were treated within the protocol. Overall response rate was 63% (partial remission: 19 of 30) patients. Median locoregional, distant, overall progression-free survival was 20.5, 10.9, and 8.5 months. Median overall survival was 19.5 months, with an estimated 1- and 2-year survival of 66.7% and 34.9% respectively. Stage (IIIA vs IIIB) and histologic subtype did not have a significant impact on survival rates in our patients. Treatment was tolerated well with only mild toxicity (°3 pneumonitis: 3.3%, any °3 acute toxicity: 36.7%). CONCLUSIONS: Combined radioimmunotherapy with cetuximab was safe and feasible, especially in elderly patients with multiple comorbidities. A more intensified regimen warranted investigation.
Gesehen am 05.07.2022